(3GdEjVGM aj CSQGQ GdfcGMs - (3GdTjQGRj,J (B774 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj HOC Ndb GdEfSGf ef Wjf, hLYd fSdg ef SdGdI ef eGA egjf s
(3BNQgG (B:s
(3JeJ hcedJ GdJPcQI GdeHGQcI GdeTJedI Ydi PcQ RjGOI GdHGg hGdeYGLjf hGdeShMGJ hZjQgG ef GdCOhjI GdfGaYI ddQLd hGdeQCI LYdg Gddg NGdUkG dhLgg GdcQje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B407 - (3U(B447s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B34 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B209 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B310 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(127) s
Keywords: (3GdWHs